Secondary-traumatic stress and academic self-concept in children of veterans: A cross-sectional study - Morteza Hamzeh; Masoumeh Taheri; Reza Kolbadi; Reza Moradi (Journal of Nursing Advances in Clinical Sciences)
This study aimed to evaluate the relationship between secondary traumatic stress and academic self-concept in children of veterans. This cross-sectional study, conducted in 2017 within Mazandaran province, Iran, focused on 150 children of veterans diagnosed with post-traumatic stress disorder. The instruments utilized for data collection in this investigation encompass demographic variables (such as gender, age, children's education level, father's education, mother's education, father's occupation, mother's occupation, and father's veteran percentage), the secondary traumatic stress scale, and the academic self-concept questionnaire. The mean scores for secondary traumatic stress and academic self-concept among children of veterans were 43.97 (SD=13.8) and 40.52 (SD=17.09), respectively. Furthermore, a statistically significant correlation was observed between secondary traumatic stress and academic self-concept, indicating that an increase in secondary traumatic stress was associated with a decrease in academic self-concept (P<0.01). The findings of this study underscore a discernible correlation between secondary traumatic stress and the academic self-concept observed in the children of veterans. Notably, academic success emerges as a significant factor contributing to the enhancement of self-concept among this demographic.